Sensitivities to juvenile hormone and ecdysteroid in the diapause larvae of Omphisa fuscidentalis based on the hemolymph trehalose dynamics index - Singtripop T. (2014)
The final instar larva of the bamboo borer, Omphisa fuscidentalis, is in diapause for 9 months from September to the following June. Trehalose and ecdysteroid concentrations in hemolymph were measured through the larval diapause period and in the pupal stage. The ecdysteroid concentration remained low until November, followed by a gradual increase to about 30 ng/ml in May. The trehalose concentration remained at levels ranging between 40-50 mM until May, and decreased to an almost undetectable level after pupation. Since a juvenile hormone analogue (JHA), methoprene, is capable of terminating diapause by stimulating larval prothoracic glands, we examined its effects on ecdysteroid and trehalose concentrations in larvae in December and February. The hemolymph ecdysteroid increased more quickly in February than in December, indicating that the sensitivity of the prothoracic glands to JHA increased towards the end of diapause termination. Similarly, hemolymph trehalose in February decreased within a few days after JHA application, while in December the decrease occurred in the third week. Exogenous 20-hydroxyecdysone (20E) caused a decrease in trehalose concentration in a dose-dependent manner. The effective dose of 20E, however, did not change from January until April, implying that the sensitivity of tissue(s) to 20E may not change until the end of diapause. Taken together, our results suggest that the sensitivities of tissues to JH and 20E do not increase simultaneously with the progress of diapause development and that termination of larval diapause is not associated simply with the restoration of hormone deficiencies. © 2002 Elsevier Science Ltd. All rights reserved.